Comparison of "early gastric cancer" in Britain and Japan. Issue 1 (January 1978) - Evans, D M; Craven, J L; Murphy, F; Cleary, B K
Abstract : Before the introduction of endoscopy, four out of 720 cases of gastric cancer were diagnosed before the cancer had breached the muscularis propia, an incidence of 0.5%. Using endoscopy and endoscopic biopsy, 10 out of 101 cases of gastric cancer were diagnosed at this "early" stage, an incidence of 10%. Their clinical, morphological, and histological characteristics are compared with those of Japanese "early gastric cancers" and reveal a remarkable similarity. The results of this study suggest that a higher proportion of British gastric cancers could be diagnosed at an "early" stage by more intensive investigation of dyspeptic patients using up to date radiological techniques, fibreoptic endoscopy, and endoscopic biopsy.